On Saturation of Linear Summation Methods for Fourier Series in the Spaces S_φ ^p - Shydlich, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We consider the problem of the saturation of linear summation methods for Fourier series in the spaces S_φ ^p, р > 0. We show that the saturation of a linear method and the saturation order are independent of the parameters X, ϕ, and p that define the space S_φ ^p(X).